Cross-border Acquisition and Corporate Governance: Evidence from Chinese firms - Zhou, Yaqian (2013)
This paper shows that the relationship between firm performance and corporate governance. The sample consists of 316 cross-border Chinese listed companies and the period of 1991-2012. Results of this study show that there would be a significant decrease in firm performance after the acquisition of the target firm compared with the value before M&A. Also, our evidence shows that ownership concentration, board size and CEO duality all have a negative and significant relationship with firm performance. However, we find no evidence to support the relationship between state-owned ownership, board compensation and company performance.